ANALISIS PENDAPATAN USAHA TERNAK DI KECAMATAN HINAI KABUPATEN LANGKAT - Julpanijar Julpanijar; Hasnudi Hasnudi; Abdul Rahman (JURNAL AGRICA, 2016)
The establishment of the regional autonomy policy to encourage each region to be able to develop competitive commodities where North Sumatra province government develop the livestock sector was goat. The aim of this study is to know the factors affected revenue, feasibility and strategy development. The study area is Hinai subdistrict, Langkatdistricts, the method used in this research is multiple linear regression, the R / C ratio, and a SWOT analysis. The research results show that the cost of breeding stock, feed and labor affect revenue, goat raising feasible with R / C ratio of 2.53 and Strategy SO uses (power to take advantage of opportunities) gave the highest score (4.26) in an effort to increase revenue Goat breeders.Keyword: Income, R/C ratio, SWOT, breeder